Campaña para posicionar Alpina como empresa preocupada por la responsabilidad social en la comunidad de Machachi - Domínguez Barba, Carolina de los Ángeles (2020)
The aim of this study is to publicize the activities carried out by the brand Alpina, as part of their responsibility to societal stewardship towards the environment and culture, focusing on the community of Machachi. This study is currently relevant because the poor perception the public has towards industrial agriculture and livestock, which currently has been publicly rejected by the community. Through the research process we were able to determine the various factors that influence the poor perception towards the Alpina brand. Additionally, we have uncovered the resources available in order to improve bilateral communication between the client and the public. The research determined that there are two audiences in question, with each group requiring different forms of communication. The campaigns focus is to change the poor perception the Machachi people possess towards the Alpina industrial factory which has been in the city since 2003. We hope to achieve this through varying revenues of communication and perception shifting programs.